A efetividade do direito à moradia e a atuação do Ministério Público - Leite, Luis Felipe Tegon Cerqueira (2017)
The present study will analyze, under a human rights approach, the effectiveness of the right to housing and the role of the Public Prosecution Service. We will begin by presenting the Brazilian land tenure history and the characteristics of its urbanization, therefore we will be able to analyze the juridical framework of property, addressing the social function of ownership and possession. Next, we will turn to the analysis of the right to housing, which, in the case of social right, presents challenges regarding applicability, practical limitations, coexistence with other rights that need to be effective in the context of scarce resources and retraction state-owned. Then, we will present the content of the right to housing according to the formulation developed in the international scope and under the national legal order. Finally, we will make considerations about the Public Prosecution's means to implement the right to housing